The Influence of Motivation and Discipline on Employee Performance in the Public Sector in Bandung - Hasnakamilah, Anan; Purnomo, Yudiyanto (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The pivotal role of employees as the most vital actors within an organization is underscored by numerous scholars. This research was conducted at the Bandung City Human Resources Development Personnel Agency (Badan Kepegawaian Pengembangan Sumber Daya Manusia or BKPSDM). The aim of this research is to determine the influence of motivation and work discipline on employee performance at the BKPSDM both partially and simultaneously. The method used consists of descriptive and associative methods through a survey approach. The sample for this research consists of 103 respondents. Sample collection was carried out using sampling techniques or saturation calculations. Data was obtained by distributing questionnaires using an online system via Google Form and further strengthened through direct interviews. The research results show that motivation has a positive effect on employee performance both partially and simultaneously, while work discipline has no effect on employee performance either partially or simultaneously. The findings underscore the need for targeted motivational strategies to enhance overall organizational effectiveness. This research significantly contributes to the understanding of performance determinants in public sector organizations, specifically highlighting the pivotal role of motivation.